Law and democracy : contemporary questions - Patmore, G. A. (Glenn Anthony), 1961-; Rubenstein, Kim (Australian National University Press, 2014)
Law and Democracy: Contemporary Questions provides a fresh understanding of law's regulation of Australian democracy. The book enriches public law scholarship, deepening and challenging the current conceptions of law's regulation of popular participation and legal representation.